STRATEGI PENGEMBANGAN MODAL SOSIAL UNTUK PENINGKATAN KEBERDAYAAN PETANI KARET DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Farid Naufal Rabbani; Ahmad Rifai; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aims are : 1) Analyze social capital, 2) Analyze empowerment, 3) Analyze the relationship of social capital and empowerment and 4) Formulate a strategy for developing social capital for the empowerment of rubber farmers in Singingi District. This research was conducted in Singingi District, Kuantan Singingi Regency. Social capital is measured by Principal Component Analysis (PCA) and Likert Scale, the empowerment of rubber farmers is measured using a Likert scale, the relationship between social capital to the empowerment of rubber farmers used rank spearman correlation analysis and formulates social capital strategies for the empowerment of rubber farmers using SWOT analysis. The results show that social capital has a high intensity with specific relationships in individuals in the group at the highest intensity. Significant relationship, correlated positively in very weak direction between social capital and the empowerment of rubber farmers. To increase empowerment through the social capital of rubber farmers, this research expects farmers to implement strategies that have been formulated primarily in the dimension of empowerment. Keywords: social capital, empowerment, rubber farmers.